PENDIDIKAN KARAKTER BERBASIS MANAJEMEN QOLBU DALAM MENGEMBANGKAN KARAKTER RELIGIUS SEBAGAI PENDIDIKAN KEWARGANEGARAAN DI PESANTREN - Budi - Putra (Citizenship Jurnal Pancasila dan Kewarganegaraan, 2018)
CHARACTER EDUCATION BASED ON QOLBU MANAGEMENT IN DEVELOPING RELIGIOUS CHARACTER AS A CIVIC EDUCATION IN PESANTREN Abstract            Character education is a very important and strategic step in building the identity of the nation and the establishment of a religious Indonesian society with the concept of Qolbu Management. The purpose of this research was to study and analyze character education based on Qolbu management in developing the religious character as Civic Education in Daarut Tauhiid Boarding School (Pesantren) under Dauroh Qolbiyah program. This research employed a qualitative approach. Data collection techniques were observation, interview, and documentation. The conclusion of the final results obtained in this research showed that character education based on Qolbu management is a character education which will always be processed by cleaning the heart and being sincere, honest, strong and tough, by performing obligatory and non-obligatory (sunnah) worships within the framework of experiential learning; in other words, learning by doing. It is because the central point of human’s actions lies in the heart in which a clean heart will be able to mold moral and religious youths.